The effects of training status on the fatigue and recovery of skeletal muscle
Highly trained cyclists, one group endurance-trained, the other sprint-trained, were subjected to a number of tests. The results of this study can be generalized to swimmers. Endurance training resulted in a delay in fatigue and less accumulation of metabolic waste products, most likely due to an enhanced ability to recruit slow-twitch muscle fibers. Sprint training increased resting muscle strength and faster recovery during the first four minutes after exercise. This recovery phenomenon in conjunction with endurance training means that athletes who are trained in dual sprint and endurance capacities will return to maximum strength values quickly. Implication: It is best to prepare the two energizing capacities in all swimmers. Since each requires different forms and frequencies of training the programming of these aspects is important. [In work published elsewhere, the argument has been made that sprint training should occur before endurance training in a practice session.]